Growth of Au Nanoparticles in NiO via Short Annealing of Precursor Material Thin Film and Optimization of Plasmonics. Issue 11 (17th August 2017) - Grammatikopoulos, Spyridon; Stamatelatos, Alkeos; Delimitis, Andreas; Sousanis, Andreas; Chrisanthopoulou, Athanasia; Trachylis, Dimitrios; Politis, Constantin; Poulopoulos, Panagiotis
Abstract : Au‐Ni‐O thin films are produced by co‐deposition of Au and Ni in a simple sputter coater with a base pressure of 2.5 × 10 −2  mbar. The as‐deposited material is comprised of a mixture of tiny grains of crystalline gold, metallic hexagonal nickel and nickel oxide. Part of the material is still amorphous. Post‐deposition annealing at 530 °C in a furnace in air leads to the formation of nanocomposite thin films of Au and NiO. The plasmonic behavior evolution was studied with annealing time between 2 min and 30 h in films with an initial thickness between 3 and 54 nm. Films with thickness of up to 10 nm show broad localized surface plasmon resonances already in the as‐deposited state, due to the presence of nanograins of gold in the dielectric matrix of NiO. Plasmonic resonances become sharp and have a blue shift tendency as the annealing time increases. This plasmonic system produced via a cost‐effective way may well be useful for a variety of technological applications. Abstract : HRTEM shows that the growth of Au nanoparticles in NiO matrix is achieved by first co‐depositing Au and Ni in rough vacuum and then annealing the precursor material in a furnace in air. This self‐assembled system of nanoparticles shows sharp LSPRs. The experimental results are calculated in the framework of Mie theory.